​​Review of microplastic pollution: a description of the impact on human health - Santamaria-Villalobos, Daniela (2025)
The current production of plastic is excessive, a fact that poses an environmental and public health challenge due to the formation of small plastic particles resulting from mechanical and thermal disintegration processes. These particles, known as micro- and nanoplastics, have been found almost ubiquitously in soil and water, and consequently, also in humans. This article aims to review the harmful effects of micro- and nanoplastics on human health. For this purpose, a literature review was carried out following the steps of a scoping review, through a search for scientific articles in the databases Web of Science, Nature, PubMed, and Scopus. A total of 75 documents that met the proposed inclusion and exclusion criteria were collected. This review confirms the presence of microplastics in the human body, which enter mainly through ingestion and inhalation. Their presence generates adverse effects in the body, including inflammation, oxidative stress, and accumulation in tissues, which could have implications for health. Although potential risks to human health have been identified, there are gaps in the analysis of long-term effects, as well as in the in-depth study of exposure to these particles according to geographic location and in the standardization of certain methods. Therefore, it is relevant to investigate the impact of micro- and nanoplastics in order to explore possible preventive measures.